Simplicity is the Ultimate Sophistication—Crosstalk of Post-translational Modifications on the RNA Polymerase II - Venkat Ramani, Mukesh Kumar; Yang, Wanjie; Irani, Seema; Zhang, Yan (Journal of molecular biology, 2021)
[Display omitted] •The largest subunit of RNA Pol II is heavily post-translational modified during transcription.•These modifications now can be accurately mapped by mass spectrometry.•The crosstalk among residue modifications results in differentiated transcriptional outcomes.•The Pol II modifications communicate with histones to ensure smooth transcription progress. The highly conserved C-terminal domain (CTD) of the largest subunit of RNA polymerase II comprises a consensus heptad (Y1S2P3T4S5P6S7) repeated multiple times. Despite the simplicity of its sequence, the essential CTD domain orchestrates eukaryotic transcription and co-transcriptional processes, including transcription initiation, elongation, and termination, and mRNA processing. These distinct facets of the transcription cycle rely on specific post-translational modifications (PTM) of the CTD, in which five out of the seven residues in the heptad repeat are subject to phosphorylation. A hypothesis termed the “CTD code” has been proposed in which these PTMs and their combinations generate a sophisticated landscape for spatiotemporal recruitment of transcription regulators to Pol II. In this review, we summarize the recent experimental evidence understanding the biological role of the CTD, implicating a context-dependent theme that significantly enhances the ability of accurate transcription by RNA polymerase II. Furthermore, feedback communication between the CTD and histone modifications coordinates chromatin states with RNA polymerase II-mediated transcription, ensuring the effective and accurate conversion of information into cellular responses.